Influence of Cryopreserved Cord Blood Serum and Fullerene C60 on Indices of Prooxidant-Antioxidant System in Rats with Myocardial Necrosis - Panov, Sergey I.; Belochkina, Irina V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):172.